Mitigasi Bencana Berbasis Kearifan Lokal di Daerah Wadaslintang Kabupaten Wonosobo - Fahrus Widodo; Suwarno Suwarno (Proceedings Series on Social Sciences & Humanities, 2022)
This research is about the mitigation or prevention of social disasters based on local wisdom that occurred in the Wadaslintang area, Wonosobo Regency. This study uses a qualitative approach. Data were collected through this research method using the method of literature study or literature study. This method was chosen because of the short research time and to find references on the basis of theories that are relevant to the cases or problems found. This study aims to determine one of the local wisdoms used to prevent social disasters. The results showed that: (a). The slamatan (tumpengan) which is given the name buceng stands for "nyebuto sing kenceng" which means praying together in earnest, which is exchanged for those present which is interpreted as friendship, mutual cooperation and kinship between members of the community so that they live safely, securely, and peacefully. (b). Wayang kulit performances at night are a means of learning for the younger generation to love the noble culture. Wayang as a spectacle (entertainment) as well as a guide (example) to be implemented in everyday life for the good things, and shunned for the bad things. The main obstacle in implementing the Merdi Desa tradition is funds (finance) because in its implementation it requires relatively large funds, and public awareness of contributions is decreasing.